A requirement for Fgfr2 in middle ear development. Issue 1 (4th October 2018) - Rigueur, Diana; Roberts, Ryan R.; Bobzin, Lauren; Merrill, Amy E.
Summary: The skeletal structure of the mammalian middle ear, which is composed of three endochondral ossicles suspended within a membranous air‐filled capsule, plays a critical role in conducting sound. Gene mutations that alter skeletal development in the middle ear result in auditory impairment. Mutations in fibroblast growth factor receptor 2 ( FGFR2 ), an important regulator of endochondral and intramembranous bone formation, cause a spectrum of congenital skeletal disorders featuring conductive hearing loss. Although the middle ear malformations in multiple FGFR2 gain‐of‐function disorders are clinically characterized, those in the FGFR2 loss‐of‐function disorder lacrimo‐auriculo‐dento‐digital (LADD) syndrome are relatively undescribed. To better understand conductive hearing loss in LADD, we examined the middle ear skeleton of mice with conditional loss of Fgfr2 . We find that decreased auditory function in Fgfr2 mutant mice correlates with hypoplasia of the auditory bulla and ectopic bone growth at sites of tendon/ligament attachment. We show that ectopic bone associated with the intra‐articular ligaments of the incudomalleal joint is derived from Scx‐expressing cells and preceded by decreased expression of the joint progenitor marker Gdf5 . Together, these results identify a role for Fgfr2 in development of the middle ear skeletal tissues and suggest potential causes for conductive hearing loss in LADD syndrome.